Afeksi Kualitas Produk Harga Dan Promosi Terhadap Volume Penjualan Online Beras Lokal Oleh UD Khoirun Di Dusun Rawamangun Kabupaten Buru - Arman Arman; Siti Juli Umasugi (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
This study aims to evaluate the affective effect of product quality, price, and promotion on the online sales volume of local rice by UD Khoirun in Rawamangun Hamlet, Buru Regency. The research method used was a survey with a quantitative approach using a questionnaire as a data collection instrument. The respondents taken were local rice consumers at UD Khoirun who made purchases through an online platform. The results showed that affect on product quality, price, and promotion had a significant effect on the volume of online local rice sales by UD Khoirun in Rawamangun Hamlet, Buru Regency. Product quality affect has the strongest influence on online sales volume, followed by price and promotion affect. This shows that good product quality is a major factor in influencing consumer purchasing decisions. In addition, this study also shows that promotion has a lower effect on the sales volume of UD Khoirun's local rice. Therefore, UD Khoirun needs to improve promotion strategies by utilizing social media and optimizing marketing strategies through online platforms. Improving service and communication with consumers also needs to be improved to build consumer trust and loyalty. This research is expected to provide input for UD Khoirun in increasing the sales volume of local rice online and promoting local rice products in Rawamangun Hamlet, Buru Regency. In addition, this research can also contribute to local economic development and increase public awareness of the importance of consuming quality local food products.